2009
DOI: 10.1080/13811110902835130
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and Psychopathological Risk Factors for Repetition of Attempted Suicide: A 5-Year Follow-Up Study

Abstract: The present study examines the association between repetition of suicide attempts and sociodemographic and psychopathological characteristics of patients during a 5-year follow-up period. Participants were 874 suicide attempters referred to the University Hospital of Ghent, among whom 361 (41.3%) patients were available for follow-up analysis. Within 5 years, 29.2% of those admitted for an index suicide attempt repeated non-fatal suicidal behavior. Repetition of suicidal behavior was associated with high score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…The prevalence of suicidal and self-injurious behaviours was highly variable and attributed among others to a Protective factors against suicide and non-suicidal behaviours need to be highlighted. Several sociodemographic variables-sex, education, employment and family typewere found to have significant associations with attempted suicide and suicide ideation as revealed in other research [9,11,12,[25][26][27][28]. By and large the world literature is replete with identified risk and protective factors of suicide and self-injurious behaviours including poverty, ethnicity, negative life events, stigma, previous attempts, impulsivity, drug abuse spirituality, social and family supports, job engagement and others [26,27,29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of suicidal and self-injurious behaviours was highly variable and attributed among others to a Protective factors against suicide and non-suicidal behaviours need to be highlighted. Several sociodemographic variables-sex, education, employment and family typewere found to have significant associations with attempted suicide and suicide ideation as revealed in other research [9,11,12,[25][26][27][28]. By and large the world literature is replete with identified risk and protective factors of suicide and self-injurious behaviours including poverty, ethnicity, negative life events, stigma, previous attempts, impulsivity, drug abuse spirituality, social and family supports, job engagement and others [26,27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In a 5-year follow-up study of repeaters of suicidal attempts, it was reported that high anxiety, severe depression, psychiatric symptoms and young females with low education were significantly associated with repetition of attempted suicide [12]. Similarly, the identified protective factors against suicide and self-injurious behaviour are numerous, including treatment of underlying mental disorders, alcohol and drug abuse, physical disorders and others [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that young age, female sex, low socioeconomic status, low education, being divorced, living alone or alone with a child, and high severity of psychiatric symptoms were associated with repeated suicide attempts 18,19. Furthermore, the method used during the first suicide attempt has been demonstrated to serve as an important predictor of completed subsequent attempts 20,21.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a significant positive correlation between the suicide probability and past history of suicide has been found in patients of the bipolar manic and depressive groups. Several studies show that patients with personal history of suicide attempt and family history of suicide attempts or completed suicide had increased suicidal risk and worked as vulnerability factors for suicidal behavior [39][40][41][42][43][44][45][46]. In this study, it has been found that there is a significant positive correlation between suicide probability and family history of suicide in bipolar patients during the depressive episode.…”
Section: Discussionmentioning
confidence: 73%